Mission versus ethics in 1 Corinthians 9? ‘Implicit ethics’ as an aid in analysing New Testament texts - Ruben Zimmermann (HTS Teologiese Studies/Theological Studies, 2012)
The central question concerning how mission and ethics are related arises within the context of the understanding of ethics itself and in this way often leads back to the familiar ‘indicative and imperative’ model. This oversimplified approach, however, is ultimately inadequate for the Pauline ethic in general and for the particular problem concerning mission and ethics. In this article, 1 Corinthians 9 was drawn upon as an example for the ‘implicit ethics’ model, a model which allows for a more nuanced presentation of the grounds and justification for behaviour and action. Through this approach it became clear that the proclamation of the Gospel does not have to be ‘unethical’; rather, it could be located and understood within the realm of the Pauline reflection on conduct. This, in turn, justified speaking of an ‘ethic of missions (activity)’ in Paul.